High efficient degradation of organic dyes by polypyrrole‐multiwall carbon nanotubes nanocomposites. (10th January 2022) - Pang, Ai Ling; Arsad, Agus; Ahmadipour, Mohsen; Azlan Hamzah, Azrul; Ahmad Zaini, Muhammad Abbas; Mohsin, Rahmat
Abstract: Over the years, there has been an emphasis on the improvement of novel materials for photocatalytic processes for practical application in treating wastewater. In this sense, the ultrasonic‐assisted in‐situ chemical polymerization route was used to synthesize polypyrrole‐multiwall carbon nanotubes (PPy‐MWCNTs) nanocomposites. The transmission electron microscopy (TEM), X‐ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X‐ray photoelectron spectroscopy (XPS), and ultraviolet visible (UV–vis) analysis were employed to study the impact of MWCNTs on the properties of PPy. TEM showed that the PPy‐MWCNTs nanocomposites consist of spherical PPy with 80 nm particle size, while the MWCNTs showed inner and outer diameters of 7 nm and 13 nm, respectively. XRD analysis showed that the crystallinity of the PPy increased with MWCNTs loading. The potential of PPy‐MWCNTs nanocomposites as photocatalysts was evaluated via the photodegradation of rhodamine B (RhB) and methylene blue (MB) dyes. The photodegradation efficiency was found to have improved with increasing MWCNTs loading. Almost 99.36% and 78.30% of RhB and MB dye degradation were achieved after 35 min of reaction for the highest loading of MWCNTs. The remarkable nanocomposite photocatalytic activity was attributed to the optical bandgap energy (Eg ) reduction with the addition of MWCNTs. These results foreshadow the potential use of the PPy‐MWCNTs nanocomposites for water purification.